Marriage Dissolution: Children's Life Experiences Through Socio-Affective Dimension - Bairon Jaramillo-Valencia; Sonia Ruth Quintero-Arrubla; Aristóteles Álvarez-Correa (Universidad Distrital Francisco José de Caldas, 2023)
This text shows how important it is to work on socio-affective dimension, keeping in mind its impact on children's life. Similarly, this research was based on the qualitative paradigm and had the ethnographic reference as a type of research; on the other hand, techniques such as the non-participant observation, the unstructured interview and the workshop were used. Among the most meaningful results, it is presented the persistent affectation that the divorce process of parents has during the socio-affective dimension development of children. Moreover, marriage dissolution is an analog issue that influence them as well, therefore respective psychological and emotional consequences are indicated.